REVISITING ENGLISH LEARNERS' ACADEMIC WRITING NEEDS - Wan Hurani Osman; Sabariah Abd. Rahim; Anna Lynn Abu Bakar; Nor Dawirah Rahman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Unlike Malaysian schools that use syllabi issued by the Education Ministry, Malaysia's public universities have full autonomy of their syllabi. English language courses and curricula in public universities are usually based on the needs of stakeholders; government, community, academicians, learners, and also parents (Avci, Ring, and Mitchelli, 2015). Traditionally, most English language courses focus on learners’ proficiency and aim to equip learners with general, social, academic, and employment language skills. In this century, there is a need to keep up with the learners’ latest needs and requirements which are closely related to technology and globalisation. This present quantitative study attempts to tap into the current needs, perceptions, and views related to academic writing in English of one of the stakeholders in a public university in Malaysia. A group of learners in a public university was given a questionnaire that contained questions related to academic writing and the English language at the undergraduate level. The findings of this study will help syllabus designers first identify the value and importance of the existing syllabi and then, if necessary, craft the syllabus based on the current needs and views of one of the university’s stakeholders.